2016
DOI: 10.1007/s10549-016-3680-8
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab improves tumor perfusion and vascular delivery of cytotoxic therapy in a murine model of HER2+ breast cancer: preliminary results

Abstract: To employ in vivo imaging and histological techniques to identify and quantify vascular changes early in the course of treatment with trastuzumab in a murine model of HER2+ breast cancer. Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) was used to quantitatively characterize vessel perfusion/permeability (via the parameter Ktrans) and the extravascular extracellular volume fraction (ve) in the BT474 mouse model of HER2+ breast cancer (N = 20) at baseline, day one, and day four following trastuzu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 44 publications
5
57
0
Order By: Relevance
“…Specifically, in the idea that anti‐angiogenic mechanisms serve to prune the leaky, underdeveloped vasculature associated with tumor angiogenesis, thus increasing the maturity of the vasculature and (potentially) increasing the observed delivery, which could then materialize as an increase in K trans . This relationship between vascular maturation and an increase in K trans has been shown previously in HER2+ tumors with other non‐vascular disrupting agents . Consistent with our analysis, Sun et al revealed a decrease in CD‐31 following Abraxane treatment at 25 mg/kg with an increase in α‐SMA in treated groups.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, in the idea that anti‐angiogenic mechanisms serve to prune the leaky, underdeveloped vasculature associated with tumor angiogenesis, thus increasing the maturity of the vasculature and (potentially) increasing the observed delivery, which could then materialize as an increase in K trans . This relationship between vascular maturation and an increase in K trans has been shown previously in HER2+ tumors with other non‐vascular disrupting agents . Consistent with our analysis, Sun et al revealed a decrease in CD‐31 following Abraxane treatment at 25 mg/kg with an increase in α‐SMA in treated groups.…”
Section: Discussionsupporting
confidence: 92%
“…An example of the error commonly encountered when performing a DCE‐MRI experiment, using a temporal resolution of 1.6 s and Gd‐DTPA, is depicted in Figure . The large error in K trans is particularly of note because of its common application in diagnosing and evaluating response in cancer . Therefore, an accurate estimate of perfusion is necessary to provide accurate predictions of tumor growth and response to therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…The observed increase in tumor oxygenation (through reduction in hypoxia) initiated by treatment with trastuzumab has the potential to enhance the effectiveness of cytotoxic radiation therapy, without increasing dose or toxic side effects. Previous research has shown that trastuzumab increases the vascular delivery of a secondary agent during this same timeframe [13]. Increasing vascular delivery and reducing hypoxia presents an opportunity to decrease metastatic potential of the tumor, while improving the treatment efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as a secondary mechanism of action, trastuzumab suppresses angiogenesis by induction of antiangiogenic factors and inhibition of proangiogenic factors. This alteration in tumor vasculature has been shown through increased vascular maturation [13], decreased release of vascular endothelial growth factor (VEGF) [13-14], and a reduction of vessel diameter and leakiness [14]. Importantly, trastuzumab-induced vascular maturation has been shown to improve perfusion and intratumoral delivery of systemic agents [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation